Literacies and the Development of Social, Critical, and Creative Thought in Textbook Activities for Primary Education in Social Sciences and the Spanish Language - Ortega-Sánchez, Delfín; Cal, Esther Sanz de la; Quintana, Jaime Ibáñez (Frontiers in Psychology, 2019)
The skills of thinking, reading conceptions and reading practice (literacy levels) found in textbook activities for the sixth year of Primary Education in Social Sciences and Spanish Language in Spain are analyzed in this paper. A mixed methodology is used to triangulate the data, integrating the critical analysis of discourse and two types of statistical analysis: descriptive (frequencies and percentages) and inferential (χ2, ANOVA, and the Mann-Whitney U Test). The results inform us of both the permanence and the strengthening of the design of an activity oriented towards the development of traditional conceptions of linguistic-cognitive reading. In the framework of education for global citizenship, the conclusion is the need for student reading practices that begin with the principles of critical literacy directed at the acquisition of social, critical, and creative thinking skills.